The supply chain information sharing path based on the internet of things - Zeng, Xiao; Yi, Jing (My University, 2024)
In the context of globalization and digitization, supply chain information sharing and circulation have become important links in supply chain management. The current difficulty in sharing supply chain information is significant, and there are issues of information asymmetry and incompleteness among co participants. In order to improve the integrity and efficiency of supply chain information sharing and enhance the competitiveness of the high supply chain, this article conducts in-depth research on the path of supply chain information sharing using Internet of Things technology. This article first analyzes the level of information sharing, influencing factors, and existing problems, then explores the Internet of Things technology, and finally establishes specific methods and means for the supply chain information sharing path through the Internet of Things technology. To verify the effectiveness of the supply chain information sharing path based on the Internet of Things, in this article, a comparison was made between the development effects of enterprise supply chains before and after applying the supply chain information sharing path based on the Internet of Things. The results show that after applying the IoT based supply chain information sharing path, the market price, production capacity, and market forecasting ability of enterprises have all increased by more than 20%. The conclusion indicates that the Internet of Things can help optimize supply chain information sharing and provide a new perspective for enterprise supply chain management and development.
Keywords: cloud computing; information sharing; internet of things; supply chain